Labour after Land Reform: The Precarious Livelihoods of Former Farmworkers in Zimbabwe. Issue 3 (26th September 2018) - Scoones, Ian; Mavedzenge, Blasio; Murimbarimba, Felix; Sukume, Chrispen
ABSTRACT: What happens to labour when major redistributive land reform restructures a system of settler colonial agriculture? This article examines the livelihoods of former farmworkers on large‐scale commercial farms who still live in farm compounds after Zimbabwe's land reform. Through a mix of surveys and in‐depth biographical interviews, four different types of livelihood are identified, centred on differences in land access. These show how diverse, but often precarious, livelihoods are being carved out, representing the 'fragmented classes of labour' in a restructured agrarian economy. The analysis highlights the tensions between gaining new freedoms, notably through access to land, and being subject to new livelihood vulnerabilities. The findings are discussed in relation to wider questions about the informalization of the economy and the role of labour and employment in a post‐settler agrarian economy, where the old 'farmworker' label no longer applies.